Effect of six weeks ubiquinol supplementation on mitochondrial respiratory function and exercise capacity in healthy males - Jarred P. Acton; Nehal S. Alsharif; Jack W. Bond; Stuart P. Cocksedge; Abbie G. Mclellan; Donald L. Peden; Mark P. Funnell; Hannah F. Dugdale; Lewis J. James; Richard A. Ferguson; Tom Clifford; Stephen J. Bailey (European Journal of Applied Physiology, 2026)
Coenzyme Q10 (CoQ 10 ) is an integral component of the mitochondrial electron transfer system. Most studies have administered the oxidised form of CoQ 10 (ubiquinone) and observed no effects on mitochondrial respiratory function or endurance exercise performance. The reduced form of CoQ 10 , ubiquinol (UQH 2 ), has greater bioavailability than ubiquinone, but the effects of UQH 2 supplementation on mitochondrial respiratory function and exercise capacity are unclear. Fifty-four healthy, recreationally active males were randomised to receive either 300 mg·day − 1 UQH 2 or placebo (PLA) for 6 weeks in a double-blind independent-group design. Before and after the supplementation period, skeletal muscle mitochondrial respiration variables and protein content of the mitochondrial leak proteins, adenine nucleotide translocase1 + 2 (ANT1 + 2) and uncoupling protein-3 (UCP-3), were assessed. In addition, participants completed a severe-intensity cycle test to exhaustion to assess time to the limit of tolerance (T Lim ) and oxygen uptake (V̇O 2 ) kinetics. Compared to pre-supplementation and PLA, UQH 2 supplementation increased plasma [CoQ 10 ] ( P < 0.05), and lowered inverse respiratory control ratio (Pre-PLA: 0.064 ± 0.034 vs. Post-PLA: 0.072 ± 0.026; Pre- UQH 2 : 0.073 ± 0.039 vs. Post-UQH 2 : 0.044 ± 0.019; P < 0.05), suggestive of improved oxidative phosphorylation coupling efficiency. There were no differences in ANT1 + 2 or UCP-3 protein content post-supplementation compared to pre-supplementation between groups ( P > 0.05). End-exercise V̇O 2 , change in V̇O 2 between 2 min and end-exercise, and T Lim were not different between groups post-supplementation ( P > 0.05). Six-weeks UQH 2 supplementation increased plasma [CoQ 10 ] and oxidative phosphorylation coupling efficiency, but did not alter mitochondrial leak proteins, T Lim or V̇O 2 kinetics during severe-intensity exercise in healthy, active males.

The effect of dietary (poly)phenols on exercise-induced physiological adaptations: A systematic review and meta-analysis of human intervention trials - Guille Martinez-Negrin; Jarred P. Acton; Stuart P. Cocksedge; Stephen J. Bailey; Tom Clifford (Critical Reviews in Food Science and Nutrition, 2022)

The effect of dietary phytochemicals on nuclear factor erythroid 2-related factor 2 (Nrf2) activation: a systematic review of human intervention trials - Tom Clifford; Jarred P. Acton; Stuart P. Cocksedge; Kelly A. Bowden Davies; Stephen J. Bailey (Molecular Biology Reports, 2021)
We conducted a systematic review of human trials examining the effects of dietary phytochemicals on Nrf2 activation. In accordance with the PRISMA guidelines, Medline, Embase and CAB abstracts were searched for articles from inception until March 2020. Studies in adult humans that measured Nrf2 activation (gene or protein expression changes) following ingestion of a phytochemical, either alone or in combination were included. The study was pre-registered on the Prospero database (Registration Number: CRD42020176121). Twenty-nine full-texts were retrieved and reviewed for analysis; of these, eighteen were included in the systematic review. Most of the included participants were healthy, obese or type 2 diabetics. Study quality was assessed using the Cochrane Collaboration Risk of Bias Assessment tool. Twelve different compounds were examined in the included studies: curcumin, resveratrol and sulforaphane were the most common ( n = 3 each). Approximately half of the studies reported increases in Nrf2 activation ( n = 10); however, many were of poor quality and had an unclear or high risk of bias. There is currently limited evidence that phytochemicals activate Nrf2 in humans. Well controlled human intervention trials are needed to corroborate the findings from in vitro and animal studies.